Effect of soil fertility management practices on nematode destroying fungi in Taita, Kenya - Wachira, Peter M; Okoth, S.; Kimenju, J.W.; Mibey, RK; Kiarie, J (2011)
The effect of soil fertility management practices on nematode destroying fungi was investigated for three seasons in Taita, Kenya. The study aimed at identifying soil fertility practice that promoted nematode destroying fungi in the soil. Field experiments were established in Taita district, the treatments comprised of Mavuno fertilizer, Triple super- phosphate and calcium ammonium nitrate (TSP+CAN), cow manure and a control where no amendments were applied. This experiment was replicated in ten farms and repeated in three planting seasons. Isolation of nematode destroying fungi carried out was using the soil sprinkle technique and the isolates were identified using the key described by Cooke and Godfrey (1964). There were significant difference (P= 1.705 x 10-06) in occurrence of the nematode destroying fungi between soil fertility treatments. The highest mean (1.6) occurrence of nematode destroying fungi was recorded in soils amended with cow manure and the least (0.7) was recorded in soils from the control plots. A mean of 0.78 was recorded in soils from both TSP+CAN and Mavuno fertilizers. Plots amended with cow manure presented the highest diversity of nematodes followed by the control, then TSP+CAN and least in Mavuno with shannon indices of 0.34, 0.15, 0.13 and 0.11 respectively. Sixty percent of all the isolated nematode destroying fungi genera were from plots treated with cow manure and only twenty percent were from plots amended with the inorganic fertilizer. The control plots recorded higher number of nematode destroying fungi compared to the soils that received inorganic fertilizers.